What to take up from the patient’s talk? The clinician’s responses to the patient’s self-disclosure of their subjective experience in the psychiatric intake interview - Savander, Enikö É.; Voutilainen, Liisa; Hintikka, Jukka; Peräkylä, Anssi (Frontiers in Psychiatry, 2024)
During psychiatric diagnostic interviews, the clinician’s question usually targets specific symptom descriptions based on diagnostic categories for ICD-10/DSM-5 (2, 3). While some patients merely answer questions, others go beyond to describe their subjective experiences in a manner that highlights the intensity and urgency of those experiences. By adopting conversation analysis as a method, this study examines diagnostic interviews conducted in an outpatient clinic in South-Finland and identifies sequences that divulge patients’ subjective experiences. From 10 audio-recorded diagnostic interviews, 40 segments were selected where patients replied to medically or factually oriented questions with their self-disclosures. The research focus was on the clinicians’ responses to these disclosures. We present five sequential trajectories that the clinicians offered third-position utterances in response to their patients’ self-disclosure of subjective experiences. These trajectories include: (1) the clinician transfers the topic to a new agenda question concerning a medical or factual theme; (2) The clinician presents a follow-up question that selects a topic from the patient’s self-disclosure of a subjective experience that may orient either toward the medical/factual side or the experiential side of the patient’s telling; (3) The clinician provides an expert interpretation of the patient’s self-disclosure of his or her subjective experience from the clinician’s expert perspective; (4) The clinician gives advice that orients mainly to a treatment recommendation or to another activity; and (5) The clinician presents a formulation that focuses on the core of their patient’s self-disclosure of his or her subjective experience from the patient’s perspective. In addition, we present what these responsive practices invoke from the patient in the next turn. We argue that an awareness of these strategies facilitates both the diagnosis and an appropriate therapeutic relationship during the psychiatric assessment interview. Finally, we discuss the clinical significance of our results regarding the patient’s agency and the clinician’s more conscious patient-centred orientation in the psychiatric assessment procedure.